Applying response surface methodology to optimise maize silage making for cattle feed - Wendra Gandhatyasri Rohmah; Bayu Firmansyah; Mas'ud Effendi; Sucipto Sucipto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2019)
One of the important ingredients in cattle feed is protein. Yet, a high quality cattle feed is influenced by the balanced concentration of protein, carbohydrates, minerals and vitamins. Agricultural waste, such as maize crop waste, can be used as potential feedstock for making cattle feed. Silage is a product resulted from fermentation process, which was mostly used as a feed source to many livestock. Silage making is functioned to preserve the quality of the feeds. Especially during dry season. Maize silage has been highlighted to be alternative feed for livestock or cattle. This study was aimed to optimise the concentration of molasses and storage time in producing high quality maize silage. The parameters measured include pH, moisture content (MC), crude protein, and crude fibre. Response Surface Methodology (RSM) with two factors was used in this study, while the optimisation was formulated using statistical software Design Expert 7.0.0. The results showed that by adding molasses of 6.97% with storage time of 240 hours, the optimum quality of maize silage was achieved, giving the value of pH (3.88), water content (23.80%), crude protein (9.01%), and crude fibre (21.67%).